SINTESIS DAN PERBANDINGAN STRUKTUR, TEKSTUR BENTONIT ALAM DAN BENTONIT TERAKTIVASI ASAM - Siregar, Sri Hilma; Irma, Wirdati (Sistem Informasi, 2016)
Bentonite is a material that has several layers, which consists of one layer of octahedral and two tetrahedral layers or commonly known as the bentonite mineral that is composed of layers of 2: 1. Bentonite nature in general is less than optimal when used as an adsorbent. This can be overcome by activating the natural bentonite either chemistry or physics. In this study, natural bentonite acid activated. Bentonite activated with HF acid with a variety of 1% -5%. Acid can damage the structure of octahedral layers in the space between the layers. Effect of activation with HF acid cause ion exchange of Al3+, Fe3+, Mg2+ with H+ ions from the acid HF so changes smectite crystalline structures. Activation of bentonite with lead acid cation exchange capacity decreased and significantly increases the specific surface area of 26.893 m2 / g (natural bentonite) to 43.167 m2 / g (activated).